Pancreatic stone protein inhibits pyroptosis of pancreatic acinar cells in sepsis-associated pancreatic injury - Liu, Pingping; Xiao, Zhenghui; Lu, Xiulan; Zhang, Xinping; Huang, Jiaotian (Frontiers in Medicine, 2025)
IntroductionSepsis-associated pancreatic injury (SPI) is characterized by an increased incidence and significantly higher mortality rates. However, its underlying pathogenesis remains inadequately understood. As an acute-phase protein secreted by the pancreas, the role of pancreatic stone protein/regenerating protein (PSP/reg) in SPI remains unclear.Materials and methodsA total of 137 patients were consecutively admitted to the pediatric intensive care unit (PICU) of Hunan Children's Hospital with sepsis were included. A sepsis-associated pancreatic injury mice model was established using cecal ligation and puncture. Pancreatic injury was assessed using HE staining. Pyroptotic pancreatic cells were evaluated via Hoechst 33342/PI staining. The expression levels of caspase-1 in the pancreatic tissues and acinar cells were determined by immunohistochemistry and immunofluorescence. Protein levels of NLRP3, caspase-1 p20, and GSDMD-N were analyzed using Western blot. The concentrations of TNF-α, IL-6, IL-1β, and IL-18 were measured by ELISA.Results and discussionChildren in dead group exhibited higher circulating PSP/reg levels compared with children in survival group. The circulating PSP/reg level in the septic shock group was significantly higher than that in the sepsis group and the severe sepsis group. The circulating PSP/reg level in the severe elevation of pancreatic amylase group was significantly higher than that in the normal pancreatic amylase group and the mild elevation of pancreatic amylase group. Administration of PSP/reg significantly mitigated pancreatic injury, as evidenced by reduced histological scores and necrotic areas. The amylase activity, the serum levels of LDH, TNF-α, and IL-6 were remarkably downregulated in PSP/reg-treated mice compared to the SPI mice. PSP/reg administration significantly alleviated the LPS-induced pyroptosis. Pyroptosis activation-associated proteins, NLRP3, Caspase-1 p20 and GSDMD-N in pancreatic acinar cells were greatly elevated following LPS stimulation, which decreased with PSP/reg treatment.ConclusionPSP/reg may exhibit protective effects by inhibiting pancreatic pyroptosis in sepsis-associated pancreatic injury model and LPS-stimulated pancreatic acinar cells.